Contralateral fatigue during severe-intensity single-leg exercise: influence of acute acetaminophen ingestion - Morgan, Paul T. (Am J Physiol Regul Integr Comp Physiol, 2019)
Exhaustive single-leg exercise has been suggested to reduce time to task failure (T(lim)) during subsequent exercise in the contralateral leg by exacerbating central fatigue development. We investigated the influence of acetaminophen (ACT), an analgesic that may blunt central fatigue development, on T(lim) during single-leg exercise completed with and without prior fatiguing exercise of the contralateral leg. Fourteen recreationally active men performed single-leg severe-intensity knee-extensor exercise to T(lim) on the left (Leg(1)) and right (Leg(2)) legs without prior contralateral fatigue and on Leg(2) immediately following Leg(1) (Leg(2-CONTRA)). The tests were completed following ingestion of 1-g ACT or maltodextrin [placebo (PL)] capsules. Intramuscular phosphorus-containing metabolites and substrates and muscle activation were assessed using (31)P-MRS and electromyography, respectively. T(lim) was not different between Leg(1ACT) and Leg(1PL) conditions (402 ± 101 vs. 390 ± 106 s, P = 0.11). There was also no difference in T(lim) between Leg(2ACT-CONTRA) and Leg(2PL-CONTRA) (324 ± 85 vs. 311 ± 92 s, P = 0.10), but T(lim) was shorter in Leg(2ACT-CONTRA) and Leg(2PL-CONTRA) than in Leg(2CON) (385 ± 104 s, both P < 0.05). There were no differences in intramuscular phosphorus-containing metabolites and substrates or muscle activation between Leg(1ACT) and Leg(1PL) and between Leg(2ACT-CONTRA) and Leg(2PL-CONTRA) (all P > 0.05). These findings suggest that levels of metabolic perturbation and muscle activation at T(lim) are not different during single-leg severe-intensity knee-extensor exercise completed with or without prior fatiguing exercise of the contralateral leg. Despite contralateral fatigue, ACT ingestion did not alter neuromuscular responses, muscle metabolites, or exercise performance.